You Might Want to Engage Your Customers, But Choose Them Wisely: The Mixed Effects of Company-Initiated Customer Engagement on Customer Loyalty - Eggert, A.; Steinhoff, Lena; Witte, C. (2015 AMA Summer Marketing Educators’ Conference Proceedings, Chicago)

The Interaction of Signals: A Fuzzy set Analysis of the Video Game Industry - Kaimann, Daniel; Cox, Joe
Customers continuously evaluate the credibility and reliability of a range of signals both separately and jointly. However, existing econometric studies pay insufficient attention to the interactions and complex combinations of these signals, and are typically limited as a result of difficulties controlling for multicollinearity and endogeneity in their data. We develop a novel theoretical approach to address these issues and study different signaling effects (i.e., word-of-mouth, brand reputation, and distribution strategy) on customer perceptions. Using data on the US video games market, we apply a fuzzy set qualitative comparative analysis (fsQCA) to account for cause-effect relationships. The results of our study address a number of key issues in the economics and management literature. First, our results support the contention that reviews from professional critics act as a signal of product quality and therefore positively influence unit sales, as do the discriminatory effects of prices and restricted age ratings. Second, we find evidence to support the use of brand extension strategies as marketing tools that create spillover effects and support the launch of new products.

The Economics of Individual Behavior in Competitive Environments: Empirical Evidence from Real-Life Tournaments - Scheel, Friedrich

Customer collectives in healthcare: The transformative potential of service to overcome consumer vulnerability - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the 39th Annual Macromarketing Conference)

Interdependent Relationships Between and among Service Providers and Customer Collectives. - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the AMA SERVSIG International Service Research Conference)

Stock Market Reactions to Customer Service Outsourcing in Manufacturing Firms - Eggert, A; Böhm, E; Cramer, C (2015 AMA Winter Marketing Educators’ Conference Proceedings)

Service transition versus service infusion: Different pathways to success for service-oriented manufacturers? - Kanuri, V; Münkhoff, E; Scheer, L. K (ISBM 2014 Academic Conference)

Selling value in business markets: Why a powerful idea often fails - Eggert, A; Haas, A; Terho, H; Ulaga, W; Münkhoff, E (ISBM 2014 Academic Conference)

The corporate marketing department - Between value and vanish - Ritter, T; Eggert, A; Münkhoff, E; Ulaga, W (ISBM 2014 Academic Conference)

Service transition: A viable option for manufacturing companies with declining financial performance? - Eggert, A; Münkhoff, E; Thiesbrummel, C (Proceedings of the 43rd European Marketing Academy (EMAC) Conference)